Assessing the dilution effect of specimen pooling on the sensitivity of SARS‐CoV‐2 PCR tests. Issue 3 (30th September 2020) - Bateman, Allen C.; Mueller, Shanna; Guenther, Kyley; Shult, Peter
Abstract: The SARS‐CoV‐2 pandemic has led to an unprecedented demand for diagnostic tests. Many studies have modeled the efficiency gains of specimen pooling, but few have systematically evaluated the dilution effect of pooling on the sensitivity of tests. Using the frequency distribution of cycle threshold ( C t ) values of our first 838 SARS‐CoV‐2 positive specimens, we modeled 100 specimens on the same frequency distribution. Given this distribution, we then tested dilutions of 1:5, 1:10, and 1:50 to find the percentage of specimens positive at each C t value with each pool size. Using the frequency distribution and the percentage of specimens positive at each C t value, we estimate that pools of 5 lead to 93% sensitivity, pools of 10 lead to 91% sensitivity, and pools of 50 lead to 81% sensitivity. Pools of 5 and 10 lead to some specimens with C t values of ≥32 becoming negative, while pools of 50 lead to some specimens with C t values of ≥28 becoming negative. These sensitivity estimates can inform laboratories seeking to implement pooling approaches as they seek to balance test efficiency with sensitivity.